2013
DOI: 10.1016/j.lungcan.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Psf3 is a prognostic biomarker in lung adenocarcinoma

Abstract: Psf3 is a member of the evolutionarily conserved heterotetrameric complex GINS (Go-Ichi-Ni-San), which consists of Sld5, Psf1, Psf2, and Psf3. Previous studies have suggested that some GINS complex members are upregulated in cancer, but the status of Psf3 expression in lung adenocarcinoma has not been investigated. The objective of the current study was to determine whether Psf3 plays a role in lung adenocarcinoma by investigating clinical samples. We investigated the status of Psf3 expression in cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…Recent studies show that several GINS components are highly expressed in different kinds of cancer and related to poor prognosis and tumor progression [9,14,15,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that several GINS components are highly expressed in different kinds of cancer and related to poor prognosis and tumor progression [9,14,15,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports have suggested that PSF1 is required for acute proliferation of cells, particularly immature cells such as stem cells and progenitor cells and that this protein is also used as a marker for the detection of cancer stem cells [6,8]. Moreover, previous studies have suggested that PSF1 and some other GINS complex members are unregulated in cancer and associated with tumor malignancy characters [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…For the assessment of the protein expression of Sirt1, samples were classified as Sirt1-positive when the ratio of stained cells in all epithelial cancer cells of a tumor tissue was >50%, and as Sirt1-negative if it was <50%. The cut-off value was set at 50%, as this value was statistically useful for this study (24). …”
Section: Methodsmentioning
confidence: 99%
“…IHC was previously performed for 10 cancer-related proteins (including CDC45, HIF1, psf3, E-cadhelin and necl5) with the same paraffin-embedded specimens of the 125 cases investigated in the present study. The correlation between their expression in cancer cells compared with Sirt1 expression was also examined, however, only HIF1 showed a statistically significant different (P<0.05) (2426). …”
Section: Methodsmentioning
confidence: 99%
“…The advance of these technologies allows molecular diagnostic biomarkers for the detection of lung cancer in addition to computed tomography (CT) screening (47). For example, the utility of epidermal growth factor receptor (EGFR) mutation testing is strongly recommended (8) in clinical practice.…”
Section: Introductionmentioning
confidence: 99%